2016
DOI: 10.1016/j.jadohealth.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

#Proana: Pro-Eating Disorder Socialization on Twitter

Abstract: Findings suggest that profiles which self-identify as Pro-ED express disordered eating patterns through tweets and have an audience of followers, many of whom also reference ED in their own profiles. ED socialization on Twitter might provide social support, but in the Pro-ED context this activity might also reinforce an ED identity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 27 publications
3
106
0
Order By: Relevance
“…A qualitative study of pro-anorexia bloggers, for example, suggests that the stigma associated with eating disorders offline is what drives many individuals to such sites; once there, however, powerful norms regarding language and behavior may reinforce individuals’ eating disorder identities (Yeshua-Katz 2015). Studies also highlight the ease and scale with which such content can be socialized, indicating that many pro-eating disorder Twitter accounts have hundreds of followers, approximately half of whom have also posted pro-eating disorder tweets (Arseniev-Koehler et al 2016). …”
Section: Peer Influencementioning
confidence: 99%
“…A qualitative study of pro-anorexia bloggers, for example, suggests that the stigma associated with eating disorders offline is what drives many individuals to such sites; once there, however, powerful norms regarding language and behavior may reinforce individuals’ eating disorder identities (Yeshua-Katz 2015). Studies also highlight the ease and scale with which such content can be socialized, indicating that many pro-eating disorder Twitter accounts have hundreds of followers, approximately half of whom have also posted pro-eating disorder tweets (Arseniev-Koehler et al 2016). …”
Section: Peer Influencementioning
confidence: 99%
“…Syed-Abdul et al [41] study anorexia-related misinformation propagated through YouTube videos. Arseniev-Koehler et al [3] find that many followers of pro-ED users also selfidentify with ED by studying 45 pro-ED users on Twitter. Most of these studies use qualitative methods and involve intensive manual labor in data collection and validation.…”
Section: Related Workmentioning
confidence: 99%
“…Analyzing such information can offer a deep insight into ED-ed individuals. Moreover, while many sites such as Facebook and Instagram have taken steps to counteract the diffusion of pro-ED content [12], Twitter has taken no actions to limit such content [3]. The latter feature makes Twitter a unique online SM platform to study ED.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, members are likely to identify strongly with these communities, making it difficult for parents or professionals to intervene. Pro-eating disorder communities are found on various social media sites, including Facebook (Teufel et al, 2013), YouTube Syed-Abdul et al, 2013), Twitter (Arseniev-Koehler, Lee, McCormick & Moreno, 2016), Instagram, Pinterest (Custers, 2015), and Flickr (Yom-Tov, Fernandez-Luque, Weber & Crain, 2012). The EU Kids Online report found that 10 per cent of 11-16-year-olds had seen pro-eating disorder content.…”
Section: Pro-eating Disorder Contentmentioning
confidence: 99%